2020
DOI: 10.15587/1729-4061.2020.196947
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Camelina oil ethyl esters as components of jet fuels

Abstract: Проведено переестерифікацію нерафінованої рижієвої олії на лужному каталізаторі із застосуванням товар ного безводного етилового спирту паливного призначен ня. Показано, що зростання вмісту вологи в спирті до 1 % призводить до низького виходу етилових естерів. Запропоновано технологічну схему виробництва дослідної партії етилових естерів рижієвої олії у лабораторних умо вах. Схема включає: приготування розчину каталізатора, переестерифікацію олії етиловим спиртом, відстоюван ня, відпарку спирту, розділення, пр… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
5
0
4
Order By: Relevance
“…The physico-chemical properties of these camelina oil ethyl esters were reported to be more similar to those typically found in jet fuel and so could potentially serve as an alternative renewable fuel for aviation. 102 Sun et al (2015), reported the production of camelina oil derived biodiesel using supercritical alcohol mixtures to improve quality and yield. A mixture of different alcohols (e.g., ethanol : 1-butanol and methanol : 1-butanol) and a range of molar ratios were studied to determine their impact on free fatty acid alkyl ester yield, the physical properties of the biodiesel and the impact of specic temperatures, pressures, and reaction times on the composition of their blend mixtures.…”
Section: Biofuel Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physico-chemical properties of these camelina oil ethyl esters were reported to be more similar to those typically found in jet fuel and so could potentially serve as an alternative renewable fuel for aviation. 102 Sun et al (2015), reported the production of camelina oil derived biodiesel using supercritical alcohol mixtures to improve quality and yield. A mixture of different alcohols (e.g., ethanol : 1-butanol and methanol : 1-butanol) and a range of molar ratios were studied to determine their impact on free fatty acid alkyl ester yield, the physical properties of the biodiesel and the impact of specic temperatures, pressures, and reaction times on the composition of their blend mixtures.…”
Section: Biofuel Productionmentioning
confidence: 99%
“…Combining linseed or soybean oil with synthetic precursors such as phthalic anhydride or pentaerythriol was reported to produce alkyd resins. However, these synthetic raw materials are not environmentally friendly due to their toxicity 101,102 and there is high demand to use alternatives such as non-food fatty acids (vegetable oils), as a raw material to produce alkyd resins. In this respect, camelina oil represents an excellent alternative raw material for synthesis of these materials.…”
Section: Alkyd Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…У попередніх роботах [3,[8][9][10][11] авторами виконано серію експериментальних досліджень, спрямованих на аналіз основних фізико-хімічних властивостей біопалив. В рамках цих досліджень було проаналізовано біопалива на основі метилових та етилових естерів ріпакової та рижієвої олій за параметрами густини, в'язкості, фракційного складу, температури кристалізації, температури спалаху та деяких інших характеристик [3,8,11].…”
Section: аналіз останніх досліджень і публікаційunclassified
“…У попередніх роботах [3,[8][9][10][11] авторами виконано серію експериментальних досліджень, спрямованих на аналіз основних фізико-хімічних властивостей біопалив. В рамках цих досліджень було проаналізовано біопалива на основі метилових та етилових естерів ріпакової та рижієвої олій за параметрами густини, в'язкості, фракційного складу, температури кристалізації, температури спалаху та деяких інших характеристик [3,8,11]. Результати показали достатній рівень сумісності традиційних авіаційних палив та біодобавок, задовільні фізико-хімічні властивості біопалив, які відповідають вимогам нормативних документів, а також покращення окремих експлуатаційних властивостей.…”
Section: аналіз останніх досліджень і публікаційunclassified